Is it Accurate to Separate Glucose-6-Phosphate Dehydrogenase Activity in Neonatal Hyperbilirubinemia as Deficient and Normal? - Hasan Kilicdag; Zeynel Gökmen; Servet Ozkiraz; Hande Gulcan; Aylin Tarcan (Pediatrics and Neonatology)
The aim of this study was to investigate glucose 6-phosphate dehydrogenase (G6PD) activity in term and late preterm babies with severe neonatal hyperbilirubinemia and its relationship to the severity and treatment of this disorder, regardless of level of G6PD activity (deficient/normal). Methods: A total of 529 term and late preterm (≥35 weeks) infants (228 female, 301 male) who were diagnosed with severe hyperbilirubinemia were included in this study. In each case, serum was collected to evaluate blood group, direct Coombs' test, complete blood cell count, total and direct bilirubin, thyroid-stimulating hormone, and G6PD activity. A partial correlation analysis was carried out to assess the relationship between G6PD activity and total bilirubin levels. Results: A significant correlation was found between the severity of hyperbilirubinemia and G6PD activity in both males and females. Male neonates who had G6PD levels <12 U/g Hb required more phototherapy time than neonates who had G6PD levels ≥12 U/g Hb; and female neonates who had G6PD levels <16 U/g Hb required more phototherapy time than neonates who had G6PD levels ≥16 U/g Hb (p < 0.0001). When we analyzed only breastfed infants, a significant difference also emerged in both sexes. Decreased G6PD activity was associated with increased phototherapy time and the need for exchange transfusion. Conclusion: Routine checks of G6PD level in hyperbilirubinemic neonates are very important in providing proper medical management to prevent bilirubin-induced neurological dysfunction. Appropriate identification of G6PD (<12 U/g Hb for male infants and <16 U/g Hb for female infants) raises awareness of the severity of the condition and the necessity for immediate care of severe hyperbilirubinemic infants.